Design space analysis for supercritical CO2 radial inflow turbine stators. (1st February 2023) - Qi, Jianhui; Yang, Yueming; Han, Kuihua; Gao, Ming; Li, Yingjie; He, Suoying; Xu, Jinliang
Abstract: Radial inflow turbines(RITs) play a vital role in power generation due to their small size, compact construction and large power density, especially when applying to supercritical CO2(sCO 2 ) power cycles. Correct preliminary design of the RITs is important for enhancing the efficiency of cycles. Most preliminary design studies for RITs simply impose empirically developed angle constraints for the rotor inlet conditions instead of giving much attention to the stators. In addition, the previous design procedure can only calculate one geometry at a time, which does not allow the selection of the most suitable geometry that fits the cycle parameters and constraints. Hence, this paper presents a workflow to correctly size a stator for achieving a desired rotor inflow conditions. Then a stator design-space analysis with utilising an existing 500 kW sCO 2 rotor is conducted. Based on a number of given stator radius ratio( r 3 / r 4 ), blade number( Z s ) and blade trailing edge thickness( t 3 ), the obtained design map contains a total number of N r 3 / r 4 × N Z s × N t 3 preliminary design cases. New insights are discussed, including that the workflow is functional; the blade angles need to adjust between no-loss and loss cases; the rotor–stator interaction loss will increase the stator inlet/outlet operational parameter when guaranteeing the target rotor inlet conditions; and including of the stator losses in turbine design is significant. Graphical abstract: Highlights: A workflow to size a stator achieving given rotor inflow condition was proposed. The validity of the work-flow and influences of different losses was confirmed. Stator design maps will help the designers finding favourable stator designs. The rotor–stator interaction loss will increase the stator operational parameter.